SWOT-BASED MARKETING STRATEGY FORMULATION TO IMPROVE MICRO-ENTERPRISE COMPETITIVENESS - Aidil Purta; Sjukun; Pius Deski Manalu (Journal of Financial Management & Accounting, 2025)
Micro-enterprises play a vital role in supporting the national economy, especially in creating jobs and driving the local economy. However, amidst the increasingly dynamic market competition, many micro-entrepreneurs have difficulty increasing their competitiveness, especially in terms of marketing. This study aims to formulate a relevant and applicable marketing strategy for micro-entrepreneurs, using a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis approach. The research method used is descriptive qualitative with a case study of culinary entrepreneurs in City X. Data were collected through direct observation, in-depth interviews, and documentation of business activities. The results of the study indicate that a SWOT-based strategy—which includes the SO, ST, WO, and WT approaches—can help entrepreneurs design more targeted, innovative, and adaptive marketing steps to existing challenges. Recommended strategies include marketing digitalization, improving product quality, and collaborating with communities and other entrepreneurs. This approach not only strengthens the position of micro-enterprises in competition but also provides new hope for the sustainability and growth of their businesses in the future. Keywords:marketing strategy, SWOT, competitiveness, micro business, UMKM